Design And In Vitro Evaluation Of Floating Diltiazem Hydrochloride Tablets Based On Gas Formation - TARIQUE KHAN; SAYYED NAZIM; SIRAJ SHAIKH (International Journal of Pharma and Bio Sciences, 2011)
The gastroretentive dosage forms have potential for use as controlled-release drug delivery systems. The use of floating dosage forms is one method to achieve prolonged gastric residence times, providing opportunity for both local and systemic drug action. The present investigation involve the development and in vitro evaluation of the floating matrix tablets, which after oral administration can prolong the gastric residence time, increase the drug bioavailability. A polymer (sodium carboxymethyl cellulose or hydroxypropylmethylcellulose K4M, K15M) was added to control the drug release. The time to flotation could be controlled by the composition (type of filler, concentration of effervescent agents) and hardness of the tablet. Six different formulations were prepared i.e. D1, D2, D3, D4, D5, and D6 by varying the polymers ratio. All the formulations were evaluated for hardness, friability, weight variation, drug content uniformity, buoyancy studies, and in vitro drug release study. The formulation D4 shows 99% drug release at the end of 12 h in vitro and floating lag time was 30 sec and tablet remained buoyant throughout studies.